Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5194/fr-20-129-2017
|View full text |Cite
|
Sign up to set email alerts
|

The blueprint of the Amphiesmenoptera – Tarachoptera, a new order of insects from Burmese amber (Insecta, Amphiesmenoptera)

Abstract: Abstract. Based on a total of 14 inclusions from Burmese amber the new insect order Tarachoptera is established. The family Tarachocelidae previously described from Burmese amber and then placed in Amphiesmenoptera incertae sedis is assigned to this new order. The genus Kinitocelis gen. nov. is established to accommodate three new fossil species: K. hennigi spec. nov., K. divisinotata spec. nov. and K. brevicostata spec. nov. The new genus differs from Tarachocelis gen. nov. by the absence of androconial scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Other authors agree that the haustellum as found in Trichoptera is the only unequivocal autapomorphy of adult Trichoptera [25]. A similar structure is found in in the non-Glossatan Lepidoptera and is assumed to be present in Tarachoptera, but it is small and not visible externally [26]. The haustellum has not previously been reported in any specimen of necrotauliid; coupled with the similarity of wing venation with other basal amphiesmenopterans it has been difficult to say with any degree of certainty whether Necrotauliidae do belong to Trichoptera [18,20] or are stemamphiesmenopterans [12,14].…”
Section: Introductionmentioning
confidence: 74%
“…Other authors agree that the haustellum as found in Trichoptera is the only unequivocal autapomorphy of adult Trichoptera [25]. A similar structure is found in in the non-Glossatan Lepidoptera and is assumed to be present in Tarachoptera, but it is small and not visible externally [26]. The haustellum has not previously been reported in any specimen of necrotauliid; coupled with the similarity of wing venation with other basal amphiesmenopterans it has been difficult to say with any degree of certainty whether Necrotauliidae do belong to Trichoptera [18,20] or are stemamphiesmenopterans [12,14].…”
Section: Introductionmentioning
confidence: 74%
“…Our survey of extant scale types and a compilation of the principal morphological characteristics ( Table 1A ) suggest that most hexapods, other than Lepidoptera, may be excluded as a source for the fossil scales ( Table 1B ). There is also little affinity with the scale types of the extinct neuropteran family Kalligrammatidae ( 11 ) and Tarachoptera, a recently proposed extinct order of the Amphiesmenoptera ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tarachoptera is a newly erected stem group of Amphiesmenoptera (which also includes Lepidoptera and Trichoptera) that potentially provides important information on the origin and groundplan of wing scales in Lepidoptera ( 47 ). Using optical microscopy, TEM, and CLSM, we examined the wing scales of two newly discovered tarachopteran specimens from mid-Cretaceous Burmese amber.…”
Section: Resultsmentioning
confidence: 99%
“… ( A ) Simplified phylogeny of Amphiesmenoptera ( 47 , 55 , 56 ). ( B ) Paleogeographic distribution of Jurassic lepidopterans on a Middle Jurassic (approximately 170 Ma ago) geographic map ( 60 ).…”
Section: Discussionmentioning
confidence: 99%